Effective prism diopter for strabismus measurement: Conversion from anterior Prentice position to posterior parallel position and from glass prism to acrylic prism - Leilei Zou; Hong Liu; Shu Wang; Tian Tian; Cheng Fang; Gang Luo; Rui Liu (Indian Journal of Ophthalmology)
Purpose: In clinical ophthalmology, prisms, commonly made of glass, are labeled based on the prism diopter (PD) value measured in the anterior Prentice position. However, they are often used in the posterior parallel position for practicality, causing a discrepancy between labeled and effective PD. This study proposes a conversion tool to address this issue. Methods: Geometric optical analysis was employed to calculate the effective PD of glass prisms in the posterior parallel position. A lookup table was created to convert the labeled PD of the anterior Prentice position to the effective PD when the prism is used in the posterior parallel position. Clinical data from 162 patients with horizontal strabismus were collected to validate the method. Glass prism measurements, converted to effective PD, were compared with acrylic prism results. Results: The variations were significant in glass prism PD with rotation in the anterior Prentice position but stability in the posterior parallel position. Clinical deviations were larger with glass prisms, especially exceeding 30 PD, compared with acrylic prisms. Converted PD from glass prisms correlated well with acrylic prisms (R2 = 0.94, P = 0.002). The half-width of the 95% limit of agreement was ±12.32 PD. Conclusion: The proposed conversion table is valid, facilitating consistency between clinical and literature-based prism use in different positions and materials.